De novo Transcriptome Analysis of Sinapis alba in Revealing the Glucosinolate and Phytochelatin Pathways - Zhang, Xiaohui; Liu, Tongjin; Duan, Mengmeng; Song, Jiangping; Li, Xixiang (Frontiers in Plant Science, 2016)
Sinapis alba is an important condiment crop and can also be used as a phytoremediation plant. Though it has important economic and agronomic values, sequence data and the genetic tools are still rare in this plant. In the present study, a de novo transcriptome based on the transcriptions of leaves, stems and roots was assembled for S. alba for the first time. The transcriptome contains 47,972 unigenes with a mean length of 1,185 nt and an N50 of 1,672 nt. Among these unigenes, 46,535 (97%) unigenes were annotated by at least one of the following databases: NCBI non-redundant (Nr), Swiss-Prot, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, Gene Ontology (GO), and Clusters of Orthologous Groups of proteins (COGs). The tissue expression pattern profiles revealed that 3,489, 1,361 and 8,482 unigenes were predominantly expressed in the leaves, stems and roots of S. alba, respectively. Genes predominantly expressed in the leaf were enriched in photosynthesis- and carbon fixation-related pathways. Genes predominantly expressed in the stem were enriched in not only pathways related to sugar, ether lipid and amino acid metabolisms but also plant hormone signal transduction and circadian rhythm pathways, while the root-dominant genes were enriched in pathways related to lignin and cellulose syntheses, involved in plant-pathogen interactions, and potentially responsible for heavy metal chelating and detoxification. Based on this transcriptome, 14,727 simple sequence repeats (SSRs) were identified, and 12,830 pairs of primers were developed for 2,522 SSR-containing unigenes. Additionally, the glucosinolate (GSL) and phytochelatin metabolic pathways, which give the characteristic flavor and the heavy metal tolerance of this plant, were intensively analyzed. The genes of aliphatic GSLs pathway were predominantly expressed in roots. The absence of aliphatic GSLs in leaf tissues was due to the shutdown of BCAT4, MAM1 and CYP79F1 expressions. Glutathione was extensively converted into phytochelatin in roots, but it was actively converted to the oxidized form in leaves, indicating the different mechanisms in the two tissues. This transcriptome will not only benefit basic research and molecular breeding of S. alba but also be useful for the molecular-assisted transfer of beneficial traits to other crops.